Multi-Subject Decision-Making Analysis in the Public Opinion of Emergencies: From an Evolutionary Game Perspective - Guo, Chen; Song, Yinghua (Mathematics (Basel), 2025)
This study employs evolutionary game theory to analyze the tripartite interaction among government regulators, media publishers, and self-media participants in emergency public opinion management. We establish an evolutionary game model incorporating strategic motivations and key influencing factors; then, we validate the model through systematic simulations. Key findings demonstrate the following: ① the system exhibits dual stable equilibria: regulated equilibrium and autonomous equilibrium. ② Sensitivity analysis identifies critical dynamics: ① self-media behavior is primarily driven by penalty avoidance (g3) and losses (w2); ② media participation hinges on revenue incentives (m2) versus regulatory burdens (k); ③ government intervention efficacy diminishes on emergencies when resistance (v1 + v3) exceeds control benefits. The study reveals that effective governance requires the following: ① adaptive parameter tuning of punishment–reward mechanisms; ② dynamic coordination between information control and market incentives. This framework advances emergency management by quantifying how micro-level interactions shape macro-level opinion evolution, providing actionable insights for balancing stability and information freedom in digital governance.